3D Mesoporous van der Waals Heterostructures for Trifunctional Energy Electrocatalysis. Issue 5 (11th December 2017) - Tang, Cheng; Zhong, Ling; Zhang, Bingsen; Wang, Hao‐Fan; Zhang, Qiang
Abstract: The emergence of van der Waals (vdW) heterostructures of 2D materials has opened new avenues for fundamental scientific research and technological applications. However, the current concepts and strategies of material engineering lack feasibilities to comprehensively regulate the as‐obtained extrinsic physicochemical characters together with intrinsic properties and activities for optimal performances. A 3D mesoporous vdW heterostructure of graphene and nitrogen‐doped MoS2 via a two‐step sequential chemical vapor deposition method is constructed. Such strategy is demonstrated to offer an all‐round engineering of 2D materials including the morphology, edge, defect, interface, and electronic structure, thereby leading to robustly modified properties and greatly enhanced electrochemical activities. The hydrogen evolution is substantially accelerated on MoS2, while the oxygen reduction and evolution are significantly improved on graphene. This work provides a powerful overall engineering strategy of 2D materials for electrocatalysis, which is also enlightening for other nanomaterials and energy‐related applications. Abstract : A 3D mesoporous van der Waals heterostructure of graphene and nitrogen‐doped MoS2 is fabricated through a two‐step sequential chemical vapor deposition method. This affords an all‐round engineering of 2D materials including the morphology, edges, defects, interfaces, and electronic structure, thereby leading to robustly modified properties and greatly enhanced electrochemical activities.